Liquid Soap Formulation of Lahuna Leaf Extract (Eupatorium odoratum) and Betel Leaf Extract (Piper betle L.) and Activity Tests Against Escherichia coli - Elfira Jumrah; Rosmaniar (Al-Kimia, 2023)
Lahuna and betel are plants that have been used traditionally as medicine. The content of secondary metabolites in lahuna and betel leaves can be used as active compounds in the manufacture of liquid soap. This study aims to evaluate liquid soap formulations of lahuna leaf extract and betel leaf extract and to test its activity against Escherichia coli. The research method used was pH test, organoleptic test, homogeneity test, foam height test, water content test according to SNI 1996 and antibacterial activity test with agar diffusion method. The results showed that the liquid soap formulation was in accordance with SNI 1996 which was based on pH test, organoleptic test, homogeneity test, foam height test and water content test. Also, the liquid soap formulation has very strong activity against Escherichia coli characterized by a clear zone that is formed more than 19 mm